2019
DOI: 10.18474/jes18-30
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Molecular Research on Bed Bugs (Hemiptera: Cimicidae)

Abstract: With the resurgence and increase in infestations of the common bed bug, Cimex lectularius L. (Hemiptera: Cimicidae), across the world, there has been renewed interest in molecular research on this pest. In this paper, we present current information on the biology, medical importance, management practices, behavior and physiology, and molecular research conducted on bed bugs. The majority of molecular studies are focused towards understanding the molecular mechanism of insecticide resistance. Bed bugs are hemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…In poultry, bedbugs are a reemerging pests and can be significant pests in commercial poultry production as researches have shown that they are zoonotic for Aboviruses (Wood et al 2012, Adelman et al 2013, Basnet & Kamble 2019 and heavy infestations can cause a reduction in egg production, cloacal irritation, feather loss, and anemia (Williams et al 2012, Scanes & Toukhsati 2018. Cimicids that attack domestic poultry include Cimex lectularis in North America, Europe, and the former Soviet Union; Haemato siphoninodorus in Central America; and Ornitho coristoledoi in Brazil (Krinsky 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In poultry, bedbugs are a reemerging pests and can be significant pests in commercial poultry production as researches have shown that they are zoonotic for Aboviruses (Wood et al 2012, Adelman et al 2013, Basnet & Kamble 2019 and heavy infestations can cause a reduction in egg production, cloacal irritation, feather loss, and anemia (Williams et al 2012, Scanes & Toukhsati 2018. Cimicids that attack domestic poultry include Cimex lectularis in North America, Europe, and the former Soviet Union; Haemato siphoninodorus in Central America; and Ornitho coristoledoi in Brazil (Krinsky 2019).…”
Section: Introductionmentioning
confidence: 99%